2016
DOI: 10.1007/s00467-015-3289-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phosphorylation of JAK2-STAT5b signaling in fibroblasts from uremic children

Abstract: In this study, children with CKD undergoing PD therapy showed an impaired phosphorylation of JAK2/STAT5b signaling in fibroblasts after GH stimulation, as well as impaired IGFBP3 mRNA abundance. Both impairments may be partially responsible for the observed resistance to the growth-promoting actions of GH in chronic kidney failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our research group published an in vitro study of intracellular GH axis in children with CKD. The results showed a significant decreased JAK-2 phosphorylation and a decreased STAT-5b translocation to the nucleus, resulting in a decreased expression of target proteins such as IGFBP3 42 . These defects are consistent with Schaefer et al findings in experimental models in uremic rats, observing a decreased phosphorylation of JAK-2 and STAT-5; decreased translocation of phosphorylated STAT proteins to the nucleus and increased SOCS inhibitory proteins compared to healthy rats 43 .…”
Section: Discussionmentioning
confidence: 95%
“…Our research group published an in vitro study of intracellular GH axis in children with CKD. The results showed a significant decreased JAK-2 phosphorylation and a decreased STAT-5b translocation to the nucleus, resulting in a decreased expression of target proteins such as IGFBP3 42 . These defects are consistent with Schaefer et al findings in experimental models in uremic rats, observing a decreased phosphorylation of JAK-2 and STAT-5; decreased translocation of phosphorylated STAT proteins to the nucleus and increased SOCS inhibitory proteins compared to healthy rats 43 .…”
Section: Discussionmentioning
confidence: 95%
“…Western blot was realized as was previously published with some modifications [27][28][29]. Briefly, the renal cortex and medulla were dissected and homogenized with an Ultra-Turrax homogenizer in ice-cooled 10 mM Tris•HCl buffer at pH 7.4, supplemented with 1 mM EDTA, 1 mM EGTA, 0.25 M sucrose, 1% vol/vol Triton X-100, and a protease inhibitor cocktail (Complete Mini, Roche Applied Science).…”
Section: Western Blot Assaymentioning
confidence: 99%
“…Nevertheless, the potential genetic target is not achieved in most cases [20,21]. The defects in impaired phosphorylation of JAK2/STAT signaling and IGFBP concentrations after rhGH administration seem to persist, resulting in lower IGF-1 bioavailability than normally expected, even if sound clinical evidence is as yet missing [22]. A meta-analysis including 16 randomized controlled clinical trials suggested a dose of 28 IU/m 2 (0.35 mg/kg) per week as optimal [23], and this is the recommended and approved dose for treatment of growth failure in CKD [2,[24][25][26].…”
mentioning
confidence: 99%